1977
DOI: 10.1021/bi00637a008
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit muscle aldolase catalyzed proton exchange of hydroxyacetone phosphate with solvent

Abstract: Rabbit muscle aldolase catalyzes the exchange with solvent of all three methyl hydrogens of hydroxyacetone phosphate. Under saturating conditions, rates of the following processes have been measured: deuteration of hydroxyacetone phosphate in 2H2O (by an NMR method), tritiation of hydroxyacetone phosphate in H2O and 2H2O, and detritiation of tritiated hydroxyacetone phosphate in H2O and 2H2O. It is clear from these measurements (1) that there is no primary kinetic isotope effect and hence that hydrogen abstrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Thus, referring to Scheme , k −1 is large compared with k 2 , and the process that corresponds to k 1 / k −1 can be treated as a rapid pre‐equilibrium. Similar behavior has been observed by Pratt in the RMA‐catalyzed (RMA=rabbit‐muscle aldolase) deuteration of hydroxyacetone phosphate19 and by Westheimer in the acetoacetate decarboxylase‐catalyzed de‐deuteration reaction with [D 6 ]acetone 20. This model of a rapid pre‐equilibrium fits the kinetics of most of the ketone and aldehyde substrates shown in Tables 1–4.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, referring to Scheme , k −1 is large compared with k 2 , and the process that corresponds to k 1 / k −1 can be treated as a rapid pre‐equilibrium. Similar behavior has been observed by Pratt in the RMA‐catalyzed (RMA=rabbit‐muscle aldolase) deuteration of hydroxyacetone phosphate19 and by Westheimer in the acetoacetate decarboxylase‐catalyzed de‐deuteration reaction with [D 6 ]acetone 20. This model of a rapid pre‐equilibrium fits the kinetics of most of the ketone and aldehyde substrates shown in Tables 1–4.…”
Section: Resultssupporting
confidence: 80%
“…The lack of a large isotope effect, which would be expected if the formation of the enamine occurred in the rate determining step, probably reflects a nonsymmetrical transition state. Similar observations and interpretations have already been reported for RMA 19. It is remarkable that a catalytic antibody and highly evolved enzymes share the fine details of their catalytic mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistic studies on FDP aldolase have shown that neither Schiff base formation/hydrolysis nor C–C bond formation/cleavage is rate limiting. Instead, the slowest steps for both FDP cleavage and synthesis are associated with product release. …”
Section: Discussionmentioning
confidence: 99%
“…by a procedure similar to that reported for the synthesis of 1 -halo-3-hydroxyacetone phosphates (Silverman et al, 1975). Hydrogenolysis (Brown & Brown, 1966) of the washed intermediate dibenzyl ester yielded 440 mg (23% overall yield) of crude hydroxyacetone dihydrogen phosphate, which was purified by ion-exchange chromatography on a column of Dowex-1 (Cl) resin (Pratt, 1977). The product was quantitatively recovered from the column and contained 3% inorganic phosphate, as shown by phosphate determinations before and after ashing (Ames & Dubin, 1960), using a modification (Curthoys, 1966) of the method of Fiske & Subbarow (1925).…”
Section: Methodsmentioning
confidence: 99%